About protective rules on jurisdiction. Commentary on the judgment of the Court of Justice of 20 October 2022, case C-604/20, Roi Land Investments Ltd - Ainciburu Serna, Carlos (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This article analyzes the implications that the Judgment of the ECJ of 20 October 2022, C-604/20, Roi Land case may have. There are three issues that the Court resolves in the judgment. In the first place, it establishes the indications and relevant elements when considering whether a legal relationship in which there is no formal employment contract between the parties is or is not labor. Secondly, it resolves the issue relating to the scope of application of Regulation 1215/2012 when the defendant is or may be an employer and is not domiciled in any country of the European Union. The article explains when national legislation is applicable and under what assumptions such legislation is superseded by the provisions of the Regulation. Finally, the meaning and scope of the consumer protection forum is analyzed, particularly in connection with the concept of professional activities.